Sudden Stratospheric Warmings. (8th January 2021) - Baldwin, Mark P.; Ayarzagüena, Blanca; Birner, Thomas; Butchart, Neal; Butler, Amy H.; Charlton‐Perez, Andrew J.; Domeisen, Daniela I. V.; Garfinkel, Chaim I.; Garny, Hella; Gerber, Edwin P.; Hegglin, Michaela I.; Langematz, Ulrike; et al.
Abstract: Sudden stratospheric warmings (SSWs) are impressive fluid dynamical events in which large and rapid temperature increases in the winter polar stratosphere (∼10–50 km) are associated with a complete reversal of the climatological wintertime westerly winds. SSWs are caused by the breaking of planetary‐scale waves that propagate upwards from the troposphere. During an SSW, the polar vortex breaks down, accompanied by rapid descent and warming of air in polar latitudes, mirrored by ascent and cooling above the warming. The rapid warming and descent of the polar air column affect tropospheric weather, shifting jet streams, storm tracks, and the Northern Annular Mode, making cold air outbreaks over North America and Eurasia more likely. SSWs affect the atmosphere above the stratosphere, producing widespread effects on atmospheric chemistry, temperatures, winds, neutral (nonionized) particles and electron densities, and electric fields. These effects span both hemispheres. Given their crucial role in the whole atmosphere, SSWs are also seen as a key process to analyze in climate change studies and subseasonal to seasonal prediction. This work reviews the current knowledge on the most important aspects of SSWs, from the historical background to dynamical processes, modeling, chemistry, and impact on other atmospheric layers. Plain Language Summary: The stratosphere is the layer of the atmosphere from ∼10 to 50 km, with pressures decreasing to ∼1 hPa (0.1% of surface pressure) at the top. The polar stratosphere during winter is normally very cold, with strong westerly winds. Roughly every 2 years in the Northern Hemisphere, the quiescent vortex suddenly warms over a week or two, and the winds slow dramatically, resulting in easterly winds that are more similar to the summer. These events, known as sudden stratospheric warmings (SSWs), were discovered in the early 1950s, and today, they are observed in detail by satellites. After several decades researching SSWs, considerable progress has been made in dynamical aspects of SSWs, but our understanding of how they affect both surface weather and the upper atmosphere is incomplete. We observe that variability of the stratospheric circulation (SSWs being an extreme event) is associated with shifts in the jet stream and the paths of storms, with associated effects on rainfall and temperatures. The likelihood of cold weather spells and damaging wind storms is also affected. Almost all SSWs have occurred in the Northern Hemisphere, but there was one spectacular major SSW in 2002 in the Southern Hemisphere. Key Points: Sudden stratospheric warmings are dramatic events of the polar stratosphere that affect the atmosphere from the surface to the thermosphere Our understanding of sudden stratospheric warmings has accelerated recently, particularly the predictability of surface weather effects More observations, improved climate models, and big data methods will address uncertainties in key aspects of sudden stratospheric warmings